(untitled) (Global Journal of Medical Research, 2021)
Multiple sclerosis is an autoimmune progressive neurological disease with a diverse range of urological symptomatology, since most MS patients experience one or more moderate to severe urinary symptoms, as well as bladder and/or sexual disorders. Urologists play the director’s role in evaluating and treating these patients. Therefore, identifying and understanding the central neural processes involved in specific parts of micturition in patients with neurogenic lower urinary tract dysfunction may identify areas of interest for future intervention.